Communauté linguistique et identité régionale : le cas des Bosniaques du Sandjak - Ksenija Djordjević Léonard (Lengas, 2015)
This contribution deals with the sociolinguistic situation of Sandjak Bosnians (Serbia) –an enclave located between the Republic of Serbia and Montenegro, where the majority of the population are Muslim Bosnians. First, the geostrategic context of this territory, within Balkans and in a broader scope, will be presented. Second, main components of local identity, such as history, borders, religion, ethnic and linguistic identification of the Sandjak community will be dealt with. Third, we shall make an attempt at fathoming specific features of this linguistic community as a cross-boundary area.